Da literatura e da sociedade na obra Os corumbas, de Amando Fontes - Santos, Clodoaldo Messias dos (2010)
This is a study of the book Os Corumbas, by Amando Fontes, published in 1933, that deals with the beginning of industrialization in the industrial city, as well as the impacts suffered by the poorest. We realized that there is a series of meanings and symbolic elements in the composition of characters, passages and happenings, objects and spaces that permeate the literary speech of Amando Fontes. Our objective, through this analysis, was to reach a better understanding of the relationship between Literature and Sociology, some passages of the text and the author s intention, as well as to problematize the imaginative meanings of the story. The narrative used by Fontes clearly shows us the utilization of the literary production for the understanding of sociological aspects in the initial moments of industrialization as well as people s adaptation to this new reality